1973
DOI: 10.1246/bcsj.46.3792
|View full text |Cite
|
Sign up to set email alerts
|

Polarographic Behavior of 9-Nitroanthracene and 9,10-Dinitroanthracene in Dimethylformamide

Abstract: The polarographic behavior of 9-nitroanthracene and 9,10-dinitroanthracene has been studied in dimethylformamide. 9-Nitroanthracene shows consecutive two one-electron diffusion-controlled reduction waves followed by fast chemical reactions. 9,10-Dinitroanthracene, however, shows only one reversible two-electron diffusion-controlled wave. The effect of the supporting electrolyte cation on these reduction waves was also investigated. In alkali metal or alkaline earth metal perchlorate as a supporting electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…As already mentioned, dinitroaromatics 61c and 62c have inverted potentials in their two-electron reduction to the dianionic forms shown. ,,, …”
Section: Two-electron Reactionsmentioning
confidence: 72%
“…As already mentioned, dinitroaromatics 61c and 62c have inverted potentials in their two-electron reduction to the dianionic forms shown. ,,, …”
Section: Two-electron Reactionsmentioning
confidence: 72%
“…The electrochemistry of nitroaromatic molecules has been extensively studied. Pioneering work by Ammar and Savéant showed that, even in the presence of a conjugated bridge between two nitrophenyl groups, the difference between the first two reduction potentials rapidly decreases as the length of the bridge is increased . This study also showed that tetrakis( p -nitrophenyl)ethylene is reduced in two successive, reversible two-electron reductions; first, a two-electron transfer to gem -oriented p -nitrophenyl moieties, and then a two-electron reduction of the remaining two nitrophenyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted some time ago [4,5] that 1 shows a single pair of voltammetric peaks and that the reduction peak height corresponded to a two-electron process but the existence or degree of potential inversion was not investigated. Similarly, it was found that 2 also gives a single two-electron polarographic wave and, in this case, the stepwise nature of the reduction process was demonstrated by the ability to detect an epr spectrum for the radical anion by electrochemical generation [6,7], i.e., though there is a single reduction peak, it does not correspond to simultaneous insertion of two electrons.…”
Section: Introductionmentioning
confidence: 99%